CONTEMPORARY IJTIHAD METHOD IN DETERMINING SHARIA BUSINESS LAW: ADDRESSING LEGAL NEEDS IN AN ERA OF ECONOMIC AND TECHNOLOGICAL CHANGE - Safwan; Maulana, Nora; Fauziyah, Nurul Khansa (al-Mawarid Jurnal Syariah dan Hukum (JSYH), 2025)
Purpose - Contemporary ijtihad methods have emerged in response to the need to update and adapt Sharia law to the times. An adaptive and innovative approach is required to ensure the applied law remains relevant and meets societal needs. This research explores the method of contemporary ijtihad in determining Sharia business law in depth.Method - This research is library research with a descriptive normative approach. The research data were sourced from secondary data with documentation data collection techniques that were collected continuously until it reached saturation. The data analysis is studied through several steps, starting with data reduction and ending with data presentation and conclusion drawing.Findings - The contemporary ijtihad method in determining Sharia business law is essential for addressing Muslims' legal challenges in the modern era. In this context, ijtihad relied on classical traditions and considered social changes, culture, and scientific developments. Various methods, such as tarjihi, insya'i, and integrative ijtihad, have been used to formulate laws that suit the needs of society. These methods allow mujtahids to explore and apply Sharia principles in contemporary business contexts such as e-commerce transactions, insurance, and investment. Thus, contemporary ijtihad plays a crucial role in ensuring that Sharia business law remains relevant, dynamic, and in tune with the people's interests while adhering to the basic principles of Sharia.Research Contributions/Limitations - The research findings are essential to developing flexible and contextual Islamic legal thinking and highlighting Islamic business law issues that have not been explicitly regulated in classical texts to address the dynamic challenges of Islamic business. However, the research study is limited to Muslim-majority countries so that it can be different from countries with a more pluralistic legal system.Originality/Value - This research connects contemporary ijtihad with the practical needs of Sharia business law in the modern world to offer theoretical solutions and real applications that are useful for practitioners and academics and contribute to the application of Sharia business law that is relevant and responsive to changing times.Keywor